2000
DOI: 10.1046/j.1525-1497.2000.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Cue-dose training with monetary reinforcement

Abstract: OBJECTIVE:To assess the feasibility and efficacy of two interventions for improving adherence to antiretroviral therapy regimens in HIV-infected subjects compared with a control intervention. DESIGN:Randomized, controlled, pilot study. SETTING: Department of Veterans Affairs HIV clinic and community-based HIV clinical trials site.PARTICIPANTS: Fifty-five HIV-infected subjects on stable antiretroviral therapy regimens. Subjects were predominantly male (89%) and African American (69%), and had histories of heroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(72 citation statements)
references
References 19 publications
0
71
0
1
Order By: Relevance
“…510 Unfortunately, nonadherence is common among HIV-positive patients because of the life-long nature of HAART, 11,12 adverse events, 1315 and numerous psychosocial and economic stressors. 11,1621 Interventions to improve HAART adherence vary widely and often include education and counseling, 2225 patient reminders, 26,27 behavioral therapy, 27,28 and social support. 2830 Other interventions promote combined strategies.…”
Section: Introductionmentioning
confidence: 99%
“…510 Unfortunately, nonadherence is common among HIV-positive patients because of the life-long nature of HAART, 11,12 adverse events, 1315 and numerous psychosocial and economic stressors. 11,1621 Interventions to improve HAART adherence vary widely and often include education and counseling, 2225 patient reminders, 26,27 behavioral therapy, 27,28 and social support. 2830 Other interventions promote combined strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Contingency management approaches have shown short-term positive effects in increasing ARV adherence and lowering viral load among substance using HIV-positive patients (49-51), and have been recommended as a priority for research on HIV medical care linkage and retention (52). For economically disadvantaged HIV-positive individuals, short-term monetary incentives for adherence may prove to be one useful element in off-setting vulnerability to the environmental pressures of ARV street markets.…”
Section: Discussionmentioning
confidence: 99%
“…These studies of incentivized ART adherence have all been small, and notably, the three studies that measured adherence outcomes after cessation of the incentive intervention [2729] found that the benefits faded as early as 8 weeks later. This speaks to the difficulty of maintaining durable results for a complex behavior that requires long-term maintenance.…”
Section: Adherence and Virologic Suppressionmentioning
confidence: 99%